2021
DOI: 10.1016/j.resuscitation.2021.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with delayed enteral feeding after cardiac arrest treated with veno-arterial extracorporeal membrane oxygenation and targeted temperature management

Abstract: Introduction: While early enteral nutrition is generally preferred in critically ill patients, the optimal timing of feeding among refractory cardiac arrest patients is unknown. We examined the association between timing of enteral nutrition and patient survival and safety outcomes in patients with refractory out-of-hospital cardiac arrest (OHCA) who were treated with extracorporeal cardiopulmonary resuscitation (ECPR).Methods: We performed a retrospective analysis of 142 consecutive patients presenting with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
0
8
0
13
Order By: Relevance
“…They also found that adverse events related to enteral nutrition were not correlated with the timing of feeding initiation. However, the study involved obese patients with an average BMI ≥30 kg/m 2 , and the results may differ from those of patients with a normal BMI [ 25 ]. Martin et al [ 24 ] reported a low incidence of respiratory complications and mortality rate despite prolonged morbidity and hospitalization after early enteral nutrition in patients with an average BMI of 28.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…They also found that adverse events related to enteral nutrition were not correlated with the timing of feeding initiation. However, the study involved obese patients with an average BMI ≥30 kg/m 2 , and the results may differ from those of patients with a normal BMI [ 25 ]. Martin et al [ 24 ] reported a low incidence of respiratory complications and mortality rate despite prolonged morbidity and hospitalization after early enteral nutrition in patients with an average BMI of 28.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Затем были исключены обзоры, клинические случаи, исследования в детской когорте, рецензии на проведенные исследования. После оценки полнотекстовых ста тей и применения критериев включения отобрано 15 исследований [31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51], среди которых 8 ретроспективных и 6 проспективных обсервационных, 1 эксперимент ex vivo. Алгоритм отбора представлен на рис.…”
Section: результаты исследованияunclassified
“…В 11 исследованиях (8 ретроспективных и 3 проспективных) описывается практика НП и ее взаимосвязь с клиническими исходами [38][39][40][41][42][43][44][45][46][47][48]. В 3 проспективных исследованиях оцениваются индивидуальные потребности в энергии и белке, которые сравниваются со стандартизированными значениями энергопотребления.…”
Section: результаты исследованияunclassified
See 2 more Smart Citations